IMPROVEMENT OF STUDENT LEARNING OUTCOMES THROUGH THE IMPLEMENTATION OF DIFFERENTIATED PROBLEM BASED LEARNING (PBL) MODEL IN GRADE VII SMP N 2 WERU - Dari, Wulan; Sati, Sati; Iwan, Andayana (LPPM Politeknik Saint Paul Sorong, 2025)
This research was driven by the low level of students’ overall mastery, which did not meet the expected learning objectives. The primary goal of the study is to enhance student learning outcomes. It is categorized as classroom action research and was conducted over two cycles. Each cycle included four phases: (1) planning, (2) implementation, (3) observation, and (4) reflection. In the first cycle, the Problem-Based Learning (PBL) model was applied using the Teaching at the Right Level (TaRL) approach. The second cycle involved the use of differentiated PBL, focusing on the topic of ecosystem component interactions. The study involved seventh-grade students from SMP N 2 Weru as the research subjects. The findings reveal that in Cycle I, student scores ranged from 27 to 97, with 57% achieving mastery. In Cycle II, scores ranged from 47 to 93, with mastery increasing to 77%. These results indicate an improvement in student learning outcomes following the application of differentiated PBL Keywords: Problem Based Learning, PBL, Differentiation, Learning Outcomes. Abstrak Riset ini dilatarbelakangi olah ketuntasan klasikal peserta didik yang berada di bawah Ukuran pencapaian tujuan pembelajaran Penelitian ini dilaksanakan guna Upaya untuk memperbaiki prestasi belajar siswa dilakukan melalui penelitian tindakan kelas yang terdiri dari dua tahap siklus.. Proses dalam setiap siklus terbagi menjadi empat bagian, yaitu 1) perencanaan; 2) pelaksanaan; 3) observasi ;dan 4) refleksi. Siklus I yakni mengimplementasikan model PBL dengan pendekatan TaRL sedangkan siklus II mengimplementasikan PBL berdiferensiasi pada materi interaksi anatar komponen penyusun ekosistem. Sampel penelitian ini adalah peserta didik kelas VII SMP N 2 Weru. Hasil penelitian menunjukkan data siklus I dengan perolehan nilai max yakni 97, nilai min yakni 27 dengan ketuntasan klasikal yakni 57% sedangkan pada siklus II memperoleh nilai max 93, nilai min 47 dengan ketuntasan klasikal yakni 77%. Dari data tersebut diperoleh kesimpulan bahwa hasil belajar peserta didik menalami setelah diterapkannya PBL berdirensiasi